AN ANALYZE STUDENTS’ VOCABULARY MASTERY AT THE SECOND GRADE OF MTS-TI BATU BELAH IN ACADEMIC YEAR 2016/2017 - Widya Hasanah (Journal of English Language and Education, 2018)
The objective of the research is to describe how the students’ vocabulary mastery at MTS-TI Batu Belah. The subject of this research consist of 26 students of the second grade. The method of this research is descriptive research. The researcher used two instruments, those were test and questionnaire. Based on the data analysis, it showed that the average of the students’ achievement in vocabulary was 77. It was categorize in good level. Furthermore, the students’ responses showed that 65% students like to learn English. Meanwhile, 35% students didn’t like English. 38% students tried to guess new vocabulary before used dictionary. Meanwhile, 62% students felt difficult to get meaning without used dictionary. 50% students felt easy to understand the meaning of vocabulary. Meanwhile, 50% students didn’t understand about meaning of the vocabulary in English. 31% students felt easy to use appropriate word. Meanwhile, 69% students didn’t understand to use appropriate word.